Survei Permainan Tradisional dalam Pembelajaran Pendidikan Jasmani di Sekolah Dasar Se-Kecamatan Air Priukan Kabupaten Seluma - Wibowo, Tito Parta; Pranata, Edho (Educative Sportive, 2020)
The problem of this thesis is how the traditional game in Physical Education learning in each school in the Air Priukan Subdistrict. The purpose of this study is to find out the traditional game in Physical Education learning in each school. Air Priukan Subdistrict, Seluma District. Elementary School. The sampling technique used was the total sampling method, namely all elementary school physical education teachers throughout the Air Priukan Subdistrict, Seluma District, totaling 14 people from 14 elementary schools. The sampling technique uses random samples or random samples. Data collection in this study uses a survey method. Data collection techniques in this study are documentation and research. Documentation is used to obtain accurate data about the traditional game process in physical education learning in Primary Schools in Air Priukan Subdistrict, Seluma District. used is descriptive with percentages.